A general salt-resistant hydrophilic/hydrophobic nanoporous double layer design for efficient and stable solar water evaporation distillation. Issue 6 (12th September 2018) - Yang, Yawei; Zhao, Hongyang; Yin, Zongyou; Zhao, Jianqiu; Yin, Xingtian; Li, Na; Yin, Dandan; Li, Yannan; Lei, Bo; Du, Yaping; Que, Wenxiu
Abstract : A unique hydrophilic/hydrophobic nanoporous double layer structure was designed for efficient and stable solar water evaporation distillation. Abstract : A novel and elegant hydrophilic/hydrophobic nanoporous double layer structure was designed and developed for efficient long-term water desalination. It contained a hydrophobic salt-resistant hierarchical layer of well-defined Cu2 SnSe3 (or Cu2 ZnSnSe4 ) nanosphere arrays for broad solar harvesting and water vapor evaporation, and a hydrophilic filter membrane for continuous water supply and vapor generation. The as-fabricated self-floatable devices achieve remarkable solar water evaporation performances (average evaporation rate: 1.657 kg m −2 h −1 and solar thermal conversion efficiency: 86.6% under one sun) with super stability for water distillation from seawater and wastewater containing organic dyes, heavy metals and bacteria.